Investigation of the catalytic performance of coal gangue char on biomass pyrolysis in a thermogravimetric analyzer and a fixed bed reactor. (15th November 2022) - Du, Shilin; Mao, Songbo; Guo, Feiqiang; Dong, Kaiming; Shu, Rui; Bai, Jiaming; Xu, Liya; Li, Dong
Highlights: Coal gangue rich in metals was used to prepare char-supported catalysts. Coal gangue char can reduce the activation energy required for pine pyrolysis. The yield of gas increased with the increase of the coal gangue char mass ratio. The liquid product yields decreased by 19.01% at PS and CG mass ratio of 1:2. Abstract: Developing low-cost and high-performance catalysts is an important part of the development of biomass pyrolysis technologies. In this study, the coal gangue rich in metals was used to directly prepare a char-supported catalyst, and metals in coal gangue were hoped to act as catalytic sites for in-situ biomass catalytic pyrolysis and secondary tar cracking. The influence of coal gangue char on pine pyrolysis behavior and kinetics was investigated in the thermogravimetric analyzer and a fixed bed reactor. The thermogravimetric analysis showed that the addition of coal gangue char caused the movement of the initial weight loss temperature and the maximum weight loss peak of the samples to the high-temperature region. With the increase of the coal gangue char mass ratio, lower apparent activation energies of the samples were achieved in the conversion range of 0.2–0.8. Through fixed-bed isothermal pyrolysis experiments, it was found that the yield of gas increased with the increase of the coal gangue char mass ratio, while the tar yield decreased quickly. The yield of H2 and CO was significantly improved by the coal gangue char, further confirming the catalytic performance of coal gangue char on the cracking of tar molecules.